The Evolution of Fashionable Products in Online Retailing with the Focus on Amazon and Flipkart - Ganatra, Aneri; Kalal, Prince; Vidani, Jignesh (MultiTech Publisher, 2024)
This paper examines the dynamic development of fashion products in online shopping, with special focus on the giants Amazon and Flipkart Through a comprehensive secondary research perspective this study explores the changing fashion landscape of the digital marketplace, the trends embraced by these ecommerce platforms, . analyze consumer behavior and strategies The study aims to reveal key insights into the factors affecting the success and quality of apparel products in online shopping shedding light on the competitive strategies of Amazon and Flipkart manage the application Combining existing literature and market data, this study contributes to an in-depth understanding of the complex dynamics of volume